2012
DOI: 10.1097/prs.0b013e31825dcb48
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Focus Group

Abstract: This study shows significant advantages to using a social network site-based method over both Internet-based rating and traditional focus groups for evaluating facial attractiveness. The main benefits include exponential increase in raters, minimized researcher time/labor, rater scores comparable to those of the focus group method, nonnecessity of rater monetary incentives, and selectable demographics/ages of raters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…To our knowledge, this is the first study to compare NTP ideals from a population-based perspective, with data derived from nearly 4000 completed surveys. This level of statistical power is possible from the use of social-network groups (or virtual focus groups), a sampling method validated by Popenko et al 10 To our knowledge, this is also the first study to acknowledge rotation as having a mathematical effect on NTP ratio calculations. Although the study by Devcic et al 6 used populationbased methods to indirectly ascertain relationships between the methods examined here, it did not control for features other than the nasal profile when comparing attractiveness between faces.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To our knowledge, this is the first study to compare NTP ideals from a population-based perspective, with data derived from nearly 4000 completed surveys. This level of statistical power is possible from the use of social-network groups (or virtual focus groups), a sampling method validated by Popenko et al 10 To our knowledge, this is also the first study to acknowledge rotation as having a mathematical effect on NTP ratio calculations. Although the study by Devcic et al 6 used populationbased methods to indirectly ascertain relationships between the methods examined here, it did not control for features other than the nasal profile when comparing attractiveness between faces.…”
Section: Discussionmentioning
confidence: 95%
“…This database of images has been used in previous studies. 6,9,10,16,17 The synthetic images are 50:50 composites, each derived from 2 actual lateral facial photographs. Using actual patient photographs would have required extensive written informed consent, likely deterring accrual of the sample.…”
Section: Image Database and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the modes compared in the literature are very limited. Most of the chat-based groups have been asynchronous rather than real time [7,8,12-14], and only 1 study has examined video-based groups [15], which are an increasingly common offering from market research firms. Second, almost all virtual group participants either have been drawn from panels of known Internet users [14,16] or represent specialized populations, such as college students and active military personnel [6-9,13,15,17], all of which restrict the generalizability of study findings.…”
Section: Introductionmentioning
confidence: 99%
“…Third, many studies employ weak or subjective measurements to assess virtual focus group characteristics, including expert rankings, research team commentaries, or self-reported participant preferences [4,7,9,14,16,18]. Almost no study has employed rigorous or objective measures to assess virtual group performance [15].…”
Section: Introductionmentioning
confidence: 99%